ORIENTASI PENDIDIKAN MULTIKULTURAL TERHADAP MINORITAS - Taryana Taryana (Risâlah, Jurnal Pendidikan dan Studi Islam, 2018)
Indonesia as a nation of unity in diversity, composed of various ethnic groups, cultures, religions, social strata and others, is of course, in the hope of harmony within diversities in all terms of religion, politics, security, social class and as well as in education in order to create state social justice and welfare as a reflection of the Pancasila state basis. One way to achieve the above dream is through multicultural education, as a means of building tolerance of ethnic diversity, cultural, and religion and social strata of the nation, because multicultural education is a response to the diversity of school population growth, as the demand of equal rights for every group. While in the wider sense, multicultural education includes all students regardless of their groups of origins such as religion, gender, ethnic, racial, and cultural, and social strata. Ideally, however, the concept of multicultural education, is not solely directed to the areas of race, religion, and culture. Such a focus once had been an emphasis of intercultural education that emphasizes improved understanding and tolerance of individuals who come from minority groups integrated into the community of majority. Multicultural education is actually an attitude of “caring” and willing to understand the discrepancy (difference) or the “politics of recognition”; political recognition of the existence of the people from minority groups in all cases and concerns to achieve unity in diversity.